2009
DOI: 10.1007/s11103-009-9579-6
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide transcriptome analysis of two maize inbred lines under drought stress

Abstract: Drought stress greatly affects plant growth and crop yield. To understand the transcriptome dynamics during drought stress in maize seedlings, genome-wide gene expression profiling was compared between the drought-tolerant line Han21 and drought-sensitive line Ye478 using Affymetrix Maize Genome Array containing 17,555 probe sets. The results showed that in response to drought, the Han21 line had fewer probe sets with significant expression change than the Ye478 line and both lines had a common set of ~2,600 r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
136
0
5

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 190 publications
(145 citation statements)
references
References 54 publications
4
136
0
5
Order By: Relevance
“…Up-regulation of SUT1 might be necessary to maintain phloem transport despite the decrease in Suc availability caused by increased sequestration of Suc to the vacuole, increased production of osmoprotective sugars such as raffinose, and decreased Suc production. This is consistent with the observed capacity of root growth under severe drought stress, at least in the lines with higher stress tolerance (Zheng et al, 2010), and could also apply to Arabidopsis where a similar pattern was observed. In contrast to drought and salt stress, SUT1 was found to be significantly down-regulated under heat stress in the tested monocots, while SUT4 expression showed the same response.…”
Section: Sut Regulation Is Part Of the Abiotic Stress Responsesupporting
confidence: 90%
“…Up-regulation of SUT1 might be necessary to maintain phloem transport despite the decrease in Suc availability caused by increased sequestration of Suc to the vacuole, increased production of osmoprotective sugars such as raffinose, and decreased Suc production. This is consistent with the observed capacity of root growth under severe drought stress, at least in the lines with higher stress tolerance (Zheng et al, 2010), and could also apply to Arabidopsis where a similar pattern was observed. In contrast to drought and salt stress, SUT1 was found to be significantly down-regulated under heat stress in the tested monocots, while SUT4 expression showed the same response.…”
Section: Sut Regulation Is Part Of the Abiotic Stress Responsesupporting
confidence: 90%
“…7B), but also with evaporative demand (r = 0.51 and 0.48). The QTL on bin 3.05 colocated with a gene coding for a Cysrich TM (Supplemental Table S7) with roles in stress response or stress tolerance (Venancio and Aravind, 2010) and a strong up-regulation under drought stress (Zheng et al, 2010). A QTL on bin 6.01 (84.4 Mb) showed similar pattern of allelic effects although with less effect of climatic scenarios (Fig.…”
Section: Genomic Regions Controlling Grain Yield Displayed Scenario-dmentioning
confidence: 90%
“…Hundreds of transcription factors (TFs) have been found to modulate tolerance to various abiotic and biotic stresses [23][24][25][26]. Most of these TFs, which belong to several large TF families, such as AP2/ERF, bZIP, COL, MYB, HD-ZIP, and Recently, it was found that overexpression of SNAC1, a NAC gene known to regulate tolerance to drought in rice, remarkably improved tolerance to drought and excessive salinity in ramie [47].…”
Section: Comparison Of the Stress-responsive Tfs Between This Study Amentioning
confidence: 99%